2021
DOI: 10.3390/cancers13133323
|View full text |Cite
|
Sign up to set email alerts
|

miR-92b-3p Regulates Cell Cycle and Apoptosis by Targeting CDKN1C, Thereby Affecting the Sensitivity of Colorectal Cancer Cells to Chemotherapeutic Drugs

Abstract: Colorectal cancer (CRC) is the third most common malignant tumor in the world and the second leading cause of cancer death. Multidrug resistance (MDR) has become a major obstacle in the clinical treatment of CRC. The clear molecular mechanism of MDR is complex, and miRNAs play an important role in drug resistance. This study used small RNAomic screens to analyze the expression profiles of miRNAs in CRC HCT8 cell line and its chemoresistant counterpart HCT8/T cell line. It was found that miR-92b-3p was highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In addition, its expression at T0 was significantly associated with PFS. Although no data are available about miR-92b-3p dysregulation in cutaneous melanoma, this miRNA has been reported to function as an oncomiR in different types of malignancies and to promote chemoresistance [ 42 , 43 , 44 , 45 , 46 ]. miR-485-3p was downregulated in both T0/NRs vs. T0/Rs and TP/Rs vs. T0/Rs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, its expression at T0 was significantly associated with PFS. Although no data are available about miR-92b-3p dysregulation in cutaneous melanoma, this miRNA has been reported to function as an oncomiR in different types of malignancies and to promote chemoresistance [ 42 , 43 , 44 , 45 , 46 ]. miR-485-3p was downregulated in both T0/NRs vs. T0/Rs and TP/Rs vs. T0/Rs.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al. ( 98 )found that miR-92b-3p was highly expressed by CRC HCT8/T cells and that knockdown of miR-92b-3p may attenuate the resistance of MDR HCT8/T cells to chemotherapy in vitro and in vivo . They further demonstrated that miR-92b-3p regulated the sensitivity of CRC cells to chemotherapeutic drugs by regulating the cell cycle and apoptosis (via directly targeting cyclin-dependent kinase inhibitor 1C and suppressing its expression).…”
Section: Mirnas and Drug Resistance In Crcmentioning
confidence: 99%
“…They are endogenous small RNAs with a length of 18-24 nucleotides. Usually, they can base pair with the 3' untranslated region (UTR) of target mRNAs and silence genes at the post-transcriptional level by inhibiting mRNA translation or directly causing mRNA degradation and abnormal expression often appears in the occurrence and development of tumors (29). Among which the miRNA (MiR)-let-7 family is downregulated in various types of tumor tissues and has been widely studied as a tumor suppressor gene (30,31).…”
Section: Mir-let-7c-3p Targeting On Egr-1 Contributes To the Committe...mentioning
confidence: 99%